A Yellow Sea Monitoring Platform and Its Scientific Applications - Kim, Yong Sun; Jang, Chan Joo; Noh, Jae Hoon; Kim, Kyung-Tae; Kwon, Jae-Il; Min, Yongchim; Jeong, Jongmin; Lee, Jaeik; Min, In-Ki; Shim, Jae-Seol; Byun, Do-Seong; Kim, Jinkwon; et al. (Frontiers in Marine Science, 2019)
The Yellow Sea is one of the most productive continental shelves in the world. This large marine ecosystem is experiencing an epochal change in water temperature, stratification, nutrients, and, subsequently in ecological diversity. Research-oriented monitoring of these changes requires a sustainable, multi-disciplinary approach. For this purpose, the Korea Institute of Ocean and Science Technology (KIOST) constructed the Socheongcho Ocean Research Station (S-ORS), a steel-framed tower-type platform, in the central Yellow Sea about 50 km off the western coast of the Korean Peninsula. This station is equipped with about forty sensors for interdisciplinary oceanographic observations. Since its construction in 2014, this station has continuously conducted scientific observations and provided qualified time series: physical oceanographic variables such as temperature, salinity, sea level pressure, waves, and currents; biogeochemical variables such as chlorophyll-a, photosynthetic active radiation, and total suspended particles; atmospheric variables including air temperature, wind, greenhouse gases, and air particles including black carbon. A prime advantage is that this platform has provided stable facilities including a wet lab where scientists can stay and experiment on both real-time time series and in-situ water samples. Several studies are in process to understand and characterize the evolution of environmental signals, including air-sea interaction, marine ecosystems, wave detection, and total suspended particles in the central Yellow Sea. This paper provides an overview of the research facilities, maintenance, observations, scientific achievements, and next steps of the S-ORS with highlighting this station as an open lab for interdisciplinary collaboration on multiscale process studies.